Analisis Model dan Pendekatan Dakwah Kiai Muda di Era Digital - Khairuddin Khairuddin; Bayu Pradana (Icon: Islamic Communication and Contemporary Media Studies, 2025)
Da'wah activities in the digital era are a necessity in preaching. Where da'wah activities usually utilize various digital platforms and social media such as YouTube, Instagram, TikTok, Facebook and so on. This article focuses on how young clerics such as Gus Iqdam, Gus Miftah and Gus Kautsar preach through YouTube social media. Theoretically there is a gap between the principle of a preacher who must speak well, but the three young kiai instead use it as a method in preaching. The research method in the article uses qualitative with communication theory as an analytical tool. So the use of "bad" words such as gaangan, stupid, stupid, jancuk in the da'wah carried out by the young kiai is an effort to get closer to mad'u, so that mad'u, especially millennials, can easily accept da'wah messages.